INFORMASI POTENSI PARIWISATA BERBASIS AUGMENTED REALITY (STUDI KASUS: FULAN FEHAN KABUPATEN BELU) - Charles Johanes Bala Waleng; Yohanes Suban Belutowe (Lembaga Pengembangan Kinerja Dosen, 2026)
The use of Augmented Reality (AR) technology in tourism promotion offers new opportunities for presenting destination information interactively. Fulan Fehan, a destination located in Belu Regency, East Nusa Tenggara, is known for its beautiful savanna grasslands and historical significance. However, this tourism potential has not been optimally utilized due to limited promotional efforts and a lack of engaging and easily accessible information for tourists. This study aims to design an AR-based application to address these issues by providing a visual experience through 3D animations, tourist object information, and interactive features via Android devices. The implementation of the Waterfall software development method ensures that the design process is carried out systematically, starting from requirement analysis to design and implementation. This application serves as an effective promotional medium, offering new insights for tourists and supporting increased interest in the Fulan Fehan tourist destination.